SYNTHESIS OF NEW BORON COMPOUNDS WITH AMOXICILLIN AND SOME OF ITS METAL COMPLEXES WITH USE THEM IN ANTIBACTERIAL, ASSESSMENT OF HEPATOPROTICTIVE AND KIDNEYACTIVITY, ANTICANCER AND ANTIOXIDANT APPLICATIONS - AL-JEBOURI, GHANEM SH; NOORIKHALEEL, ASMAA MOHAMMED (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: New ligand ({7-[2-amino-2-(4-hydroxyphenyl)-acetamido-3,3-dimethyl-6-oxo-2-thia-5-aza bicyclo[3,2,0]heptane-4-carboxylic boric anhydride}) with its Co (II), Ni (II) and Cu (II) complexes. And new mixed ligand copper complex was synthesized. Methods: The ligand was synthesized by the reaction of boric acid with amoxicillin (1:1) and the mixed ligand complex has been synthesized by the reaction of the ligand, 4-aminoantipyrine and Cu (II) ion (1:1:1). Results: All studied compounds were characterized by the spectral method: Fourier transform infrared, ultraviolet-visible, thermal analysis (TG and DTG), flame atomic absorption and nuclear magnetic resonance. Also CHNS, melting point, magnetic susceptibility and molar conductivity. Conclusion: According to the obtained data, all complexes were non electrolyte and the geometry was octahedral for all complexes. All synthesized compounds were tested as antibacterial agents against Escherichia Coli, Pseudomonas auroginosa as Gram-negative bacteria (G-) and Staphylococcus aureus epidermis as Gram-positive bacteria (G+). The results showed that copper complexes were more active in (10-2M) than the other compounds. The medicinal applications (hepatoprotective and kidney in serum of mice, histopathological of liver and kidney, anticancer and antioxidant in human cell were studied of the synthesized compounds and gave a good results in all tested.